SEGMENTASI PASAR JASA LAYANAN KESEHATAN BERDASARKAN MANFAAT YANG DI RASAKAN OLEH PELANGGAN JASA RUMAH SAKIT DI KABUPATEN GRESIK (STUDI PADA RUMAH SAKIT SEMEN GRESIK DAN RUMAH SAKIT PETROKIMIA GRESIK) - Farida, Nur (Fakultas Ekonomi Universitas Gresik, 2015)
Market segmentation has long been regarded as one of the most important marketing concepts are available for managers interested in marketing the product. In todayÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¢ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¾Ãƒâ€šÃ‚Â¢s competitive market. Market segmentation is a market activity which divide the market into groups of buyers who are distinguished according to different needs. The purpose of the division of market into several homogeneous market is for marketers to drive to satisfy the specific needs of each target market.Market segmentation approach involves identifying the benefits sought by different homogeneous groups, which allows the properties and the relevant request is determined and used as a source of service differentiation. This study aims to determine market segmentation Semen Gresik Hospital services and Hospital Petrokimia Gresik is formed based on the benefits perceived by the customer. This research was conducted with descriptive research approach, the sample of 110 respondents. Methods of data analysis used in this research is explanatory factor analysis, cluster analysis and cross tabulation analysis